Online Attendance Management System(OAMS) - Darius Muhumuza (Uganda Christian University, 2025)
This study explored the development of an Online Attendance System designed to streamline how attendance is recorded in educational settings. Traditional manual methods were found to be slow, error-prone, and difficult to manage over time, which created a need for a more reliable solution. The research followed a descriptive approach, beginning with gathering user requirements, and then designing, building, and testing the system. The platform was created using PHP, MySQL, HTML, and JavaScript, offering an easy-to-use interface for both lecturers and students. Information was collected through interviews, observation, and system testing to evaluate its effectiveness. Results showed that the Online Attendance System helped reduce the time spent taking attendance, minimized common recording mistakes, and made it easier to generate attendance reports when needed. The findings suggest that adopting an online attendance management system can make administrative tasks more efficient and accurate. It would be a valuable investment for institutions aiming to modernize their operations.